Fault Diagnosis of Wind-turbine Gearboxes based on Fourier Decomposition Method - Lin Jinshan; Dou Chunhong; Zhao Guangsheng; Yin Jianhua (Jixie chuandong)
The Empirical Mode Decomposition （EMD）,as an empirical method,lacks rigorous theoretical proof. For this reason,EMD in practical application is confronted by many problems,which make EMD hard to extract fault features from vibration data of complex wind-turbine gearboxes. The Fourier decomposition method （FDM） is a novel method for processing non-stationary and nonlinear signals. With a firm theoretical basis,FDM has the capability for overcoming deficiencies of EMD. The FDM is used to analyze vibration data of wind-turbine gearboxes and a method for fault diagnosis of wind-turbine gearboxes based on FDM is proposed. Application to fault diagnosis of a realistic wind-turbine gearbox shows that the proposed method can effectively diagnose faults of wind-turbine gearboxes and has a clear advantage over the method based on each of spectrum analysis,EMD and wavelet decomposition.